THE INDIGENT POPULATION OF THE REPUBLIC OF DAGESTAN - Rasulov, M A (History, Archeology and Ethnography of the Caucasus, 2017)
The author of the article analyzes the state of the indigent (poor) population of the Republic of Dagestan. The problem is very urgent in the modern period of crisis in our society due to the fact that poverty is the reason for intensification of social contradictions in it, degradation of the population, and complication of the demographic situation. The author of the article presents statistical data on average per capita income of the population of the Dagestan Republic in 2002 - 2013. Since the interval distribution of incomes does not allow to characterize accurately the number of the indigent part of the population, the distribution of income according to the minimum subsistence level is considered. A significant poverty reduction in the Republic of Dagestan during the period under consideration is shown. Besides, the article presents the median per capita income, which is used in western countries and in some republics of the former Soviet Union to estimate the level of poverty. Depending on 40%, 50%, 60% of the median, like in these countries, the relative number of the indigent population in the Republic of Dagestan and in other regions of the North Caucasian Federal District is determined, which makes it possible to determine the level of extreme poverty in the Republic of Dagestan in 2013. The author shows the ratio of the average wage of 10% of employees with the highest wage to 10% of employees with the lowest wage in the institutions of the subjects of the Russian Federation in the North Caucasian Federal District and comes to the conclusion that in 2013 the poverty level in the region was lower than in the Republic of Dagestan.